2001
DOI: 10.1159/000046047
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aldose Reductase from the Thick Ascending Limb of Henle’s Loop of Rabbit Kidney

Abstract: Background: The organic osmolyte sorbitol plays an important role in the osmoregulation of immortalized epithelial cells of the thick ascending limb of Henle’s loop (TALH) of rabbit. The intracellular sorbitol content seems to depend strongly on the extracellular osmolarity. To investigate the nature of the osmotic regulation we characterized the aldose reductase. Methods: We determined aldose reductase activity enzymatically and the content of organic osmolytes by HPLC. Results: The aldose reductase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Nevertheless, similar to results observed in our study, reduction of AR protein has been reported in mouse podocytes cultured in hyperosmolar HG medium for two weeks [35] and in arterial endothelium [36]. In turn, high glucose-induced loss of AR activity was found in epithelium from thick ascending limb of Henle's loop [37]. In our experiments, high glucose not only counteracted the activation of AR in HG-Hosm cells but also blunted the AR activity in HG-Nosm podocytes, despite upregulated enzyme protein (Figures 1, 4(a), and 4(c)).…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, similar to results observed in our study, reduction of AR protein has been reported in mouse podocytes cultured in hyperosmolar HG medium for two weeks [35] and in arterial endothelium [36]. In turn, high glucose-induced loss of AR activity was found in epithelium from thick ascending limb of Henle's loop [37]. In our experiments, high glucose not only counteracted the activation of AR in HG-Hosm cells but also blunted the AR activity in HG-Nosm podocytes, despite upregulated enzyme protein (Figures 1, 4(a), and 4(c)).…”
Section: Discussionsupporting
confidence: 90%
“…BGT1 is present in the medullary thick ascending limbs of Henle loop and the medullary collecting ducts (Miyai et al, 1996; Zhou et al, 2012a). Aldose reductase (AR) is in the loop of Henle and inner medullary collecting ducts (Terubayashi et al, 1989; Schwartz et al, 1992; Grunewald et al, 2001). SMIT1 is predominantly present in the medullary and cortical thick ascending limb of Henle's loop and in the cells of the macula densa as well as to a lesser extent in the inner medullary collecting ducts (Yamauchi et al, 1995).…”
Section: Bgt1 and Betaine In Kidneymentioning
confidence: 99%
“…The production of sorbitol via AR has consistently been documented as one of the more significant physiological functions in osmoadaptation in various parts of the kidney. Grunewald et al (2001) observed that AR played a role in osmoregulation throughout all portions of the kidney medulla, indicating a uniform dispersion of expression within the tissue. In dehydration and water conservation studies, NFAT5 and AR expression were increased in the kidneys of dehydrated rats and also in the kidneys of wood frogs during anoxia, when water conservation is essential for survival (Cha et al , 2001; Al-Attar et al.…”
Section: Discussionmentioning
confidence: 92%